Polymeric micelles with aggregation-induced emission based on microbial ε-polylysine for doxorubicin delivery. (5th January 2020) - Li, Yanhai; Gao, Feng; Guo, Jin; Ren, Peng; Tian, Zhenzhen; Bai, Jianan; Hua, Jie
Graphical abstract: Highlights: mPEG- g -Plys-TPE was synthesized by modification of ε-polylysine with PEG and TPE. mPEG- g -Plys-TPE micelles showed uniform morphology with narrow size distribution. DOX-loaded micelles showed better cytotoxicity on colon tumor cells than free DOX. Abstract: Natural polymers have shown special advantages in application as drug delivery carriers. However, microbial ε-polylysine seems to have been snubbed. In this study, we constructed a drug delivery system based on natural ε-polylysine. Amphipathic graft copolymer, methoxypoly(ethylene glycol)- graft -ε-polylysine-tetraphenylethylene (mPEG- g -Plys-TPE), was synthesized based on microbial ε-polylysine which was modified completely with PEG and TPE. MPEG- g -Plys-TPE could self-assemble into nanomicelles with stable shell-core structure. PEG served as the hydrophilic shell to provide long blood circulation and biocompatibility. TPE formed the hydrophobic core with aggregation-induced emission (AIE) effect to load drugs. The physical and chemical properties, including size distribution, morphology, stability and photoluminescent effect, were investigated in detail. In vitro drug release indicated pH-dependent patterns. Furthermore, cytotoxicity of doxorubicin (DOX)-loaded micelles against HT-29, HCT116 and SW480 was significantly higher than that of free DOX, which was explained by the mechanism of cellular uptake against tumor cells. In summary, all results suggested that mPEG- g -Plys-TPE as new type biomaterials exhibited great potential for drug delivery.